Digital Preservation Meets Cultural Heritage: A Comparative Analysis of Traditional and Digital Display Methods for Korean Ethnic Costume in China (Journal of Fiber Bioengineering and Informatics, 2025)
Despite the growing use of digital applications in cultural heritage preservation, limited research exists onthe comparative effectiveness of digital versus traditional display methods for preserving ethnic costumeheritage. This study investigates how digital technologies influence the perception of Korean traditionalcostumes among China’s Korean ethnic minority (Chaoxianzu). Using CLO3D digital modelling andquestionnaire surveys $(n = 107),$ we found that digital display methods excel in communicating costumecharacteristics through three-dimensional visualisation and multi-angle presentation, with particularlystrong evaluations for intuitiveness (81.31%) and colour representation (76.64%). Digital methodssignificantly enhance cultural understanding (75.70%) and stimulate innovative applications (70.09%),especially among younger audiences (85% positive response rate). Our findings reveal that digital andphysical display methods serve complementary rather than competing roles—digital methods excel inaccessibility and spatial representation (87.85% preferred for multi-angle observation). In comparison,traditional approaches provide essential tactile experiences, which are valued for their material experience(89.72%). Statistical analysis identifies $360^◦$ multi-angle observation $(β = 0.41)$ and magnified detailobservation $(β = 0.35)$ as the most critical technical factors affecting perception value. This researchprovides empirical evidence for developing integrated preservation strategies that combine digitaltechnologies with traditional approaches to enhance the transmission and sustainable development ofethnic costume heritage.
Keywords: Korean traditional costume; digital heritage preservation; virtual display technology; cultural perception; ethnic minority heritage.